2020
DOI: 10.1097/mpg.0000000000002676
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Gluten‐free Diet in a Celiac Pediatric Population Referred to the General Pediatrician After Remission

Abstract: Objectives: Assessment of adherence to gluten-free diet in celiac disease (CD) is generally recommended. Few data are available about consequences of transition from the referral center to the general pediatrician (GP) once remission is achieved. Methods: Adherence was assessed in patients referred to the GP for an annual basis follow-up, called back for re-evaluation. Immunoglobulin A (IgA) antitissue transglutaminase (anti-tTG) antibodies and the Biag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Adherence was assessed using the TGA IgA and Biagi Score [34]. The study found such practice is a reasonable approach to ongoing management of CeD [33]. However, in this study, age over 13 years and non-Italian ethnicity were both found to be associated with GFD non-adherence.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Adherence was assessed using the TGA IgA and Biagi Score [34]. The study found such practice is a reasonable approach to ongoing management of CeD [33]. However, in this study, age over 13 years and non-Italian ethnicity were both found to be associated with GFD non-adherence.…”
Section: Discussionmentioning
confidence: 54%
“…In a different approach, Sbravati et al [33] prospectively assessed the GFD adherence of 200 children over two intervals (at least 24 months) following transition from a single referral center to a general pediatrician once remission was achieved. Adherence was assessed using the TGA IgA and Biagi Score [34].…”
Section: Discussionmentioning
confidence: 99%
“…The GFD adherence of 200 Italian children with CD was assessed to evaluate differences as a consequence of transition from a referral center (V1) to a general pediatrician (V2) [ 52 ]. Adherence was measured using the Biagi score and the IgA TGA test at the last follow-up at V1 and at an annual follow-up at V2.…”
Section: Adherence To a Gfdmentioning
confidence: 99%
“…Several studies based on nutritional questionnaires, serological tests, and evaluating gluten immunogenic peptides in feces and urine, have reported variable gluten exposure rates in patients with CD, reaching up to 69% in adults, 64% in adolescents, and 45% in children ( Figure 1 ) despite their best efforts to avoid it. Studies reporting gluten exposure rates may compromise high rates of ongoing symptoms [ 29 , 30 , 31 ] and enteropathy [ 32 , 33 , 34 , 35 ] in patients with CD, leading to comorbidities such as anemia, severe malabsorption, and various forms of malignancies [ 36 ]. Hence, it is important to drive efforts to develop non-dietary adjunctive or alternative therapies for CD treatment [ 37 ].…”
Section: Gluten-free Diet: Challenge and Gluten Exposurementioning
confidence: 99%
“… Studies reporting gluten exposure rates in CD patients on a supposed GFD. CD, celiac disease; GFD, gluten-free diet [ 23 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. …”
Section: Figurementioning
confidence: 99%